Association of Lifestyle Changes Due to the COVID-19 Pandemic with Nutrient Intake and Physical Activity Levels during Pregnancy in Japan - Natsuki Hori (MDPI AG, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has introduced changes in our lifestyles, such as refraining from unnecessary outings. This study aimed to clarify the association of lifestyle changes due to the COVID-19 pandemic with nutrient intake and physical activity levels during pregnancy in Japan. A cross-sectional study involving 168 healthy pregnant Japanese women was conducted in 2020. Nutrient intake and physical activity levels were assessed using validated self-administered questionnaires. Participants who reported experiencing changes in both dietary habits and physical activity due to the COVID-19 pandemic were classified as the lifestyle-affected group. Analysis of covariance was used. Among primiparas, intake of the following nutrients was significantly higher in the lifestyle-affected group (n = 14) than in the unaffected group (n = 77): protein, potassium, calcium, magnesium, and vitamin B6. Among multiparas, the intake of dietary fiber and β-carotene were significantly lower in the lifestyle-affected group (n = 13) than in the unaffected group (n = 64). No significant differences in physical activity levels were observed in accordance with the lifestyle changes. These findings suggest that lifestyle changes due to the COVID-19 pandemic have positive effects on nutrient intake during pregnancy in primiparas, whereas in multiparas, these changes have negative effects.